Social support, social identification, mental wellbeing, and psychological distress in doctoral students: A person-centred analysis. Issue 1 (2nd January 2023) - Jackman, Patricia C.; Slater, Matthew J.; Carter, Esther E.; Sisson, Kelly; Bird, Matthew D.
ABSTRACT: This study extends the doctoral education literature by examining how social support and social identification, as they apply to peers, supervisors, and the academic community, are related to mental wellbeing and psychological distress in doctoral students by using person-centred analysis to create social profiles. Doctoral students ( N = 200) completed a cross-sectional survey including measures of perceived support, received support, social identification, mental wellbeing, and psychological distress. Adopting a person-centred analysis approach, we identified six distinct social profiles for mental wellbeing, and four social profiles for psychological distress. Further between-profile analysis indicated that the 'high support-identification' profile was associated with higher levels of mental wellbeing and lowest levels of psychological distress. In comparison, the 'low support-identification' profile reported significantly lower mental wellbeing and significantly higher psychological distress. Taken together, the findings demonstrate the value of person-centred analysis and offers new insights into the nuances of relationships between social support, social identification, mental wellbeing, and psychological distress in doctoral students. The theoretical and practical implications arising from this research are discussed.